1995
DOI: 10.1007/bf02112618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the optimal number of faecal specimens in the diagnosis of cryptosporidiosis in AIDS and immunocompetent patients

Abstract: This study determines the optimal number of faecal samples that should be examined in order to minimize the occurrence of false-negative results in the diagnosis of cryptosporidiosis using routine techniques. A total of 23,023 faecal samples from 10,870 patients submitted for parasitological examination were processed by the formalin-ethyl acetate concentration technique and stained using a modified Ziehl-Neelsen method. Cryptosporidiosis was diagnosed in 232 patients (2.13%), 44 of whom were infected by HIV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In particular, in UK, peaks of incidence in the spring and late autumn or early winter appear to be associated with farming activity and peak rainfall (Casemore 1990;Fayer et al 2000). In Spain, the prevalence of cryptosporidiosis is significantly higher in the autumnwinter period (October to March) with a mean of 100 cases than in the spring-summer period (April to September) with a mean of 60 cases (Clavel et al 1995). In addition, in Mediterranean area, two peaks in rainfall have been documented to occur during spring (mean value of 50 ± 6AE98 mm) and mainly in autumn (mean value of 78 ± 14 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in UK, peaks of incidence in the spring and late autumn or early winter appear to be associated with farming activity and peak rainfall (Casemore 1990;Fayer et al 2000). In Spain, the prevalence of cryptosporidiosis is significantly higher in the autumnwinter period (October to March) with a mean of 100 cases than in the spring-summer period (April to September) with a mean of 60 cases (Clavel et al 1995). In addition, in Mediterranean area, two peaks in rainfall have been documented to occur during spring (mean value of 50 ± 6AE98 mm) and mainly in autumn (mean value of 78 ± 14 mm).…”
Section: Discussionmentioning
confidence: 99%
“…2000). In Spain, the prevalence of cryptosporidiosis is significantly higher in the autumn–winter period (October to March) with a mean of 100 cases than in the spring–summer period (April to September) with a mean of 60 cases (Clavel et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The use of random diarrhea samples to measure oocyst excretion by grade, while acceptable as a diagnostic test [32,33], was not strongly predictive of clinical response. It has been suggested that quantitation for oocysts in a 24-h stool collection may be a more accurate indicator of organism load [34].…”
Section: Discussionmentioning
confidence: 99%
“…But some major pitfalls have been identified in the routine diagnosis of intestinal cryptosporidiosis [21]. Firstly, the direct microscopic examination after modified ZN staining relies on the morphologic recognition of small-sized oocysts which may be scant in number, intermittently shed, or inconsistently stained [13, 22]. This method is therefore impractical to standardize as it is influenced by the individual skills of the microscopist involved.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidiosis is most commonly diagnosed by identifying oocysts in the stool specimens of infected persons. The diagnostic difficulties arise from the fact that shedding of C. parvum oocysts is intermittent even in patients with massive diarrhea [13]. The number of oocysts present in the stool sample may not be adequate for detection and it is usually seen that oocysts are better recovered from watery stools than the formed samples [14].…”
Section: Introductionmentioning
confidence: 99%